PENGUJIAN NETRALISASI SIFAT REAKTIF BUMBU DALAM GARAM BERYODIUM DENGAN BAHAN TAMBAHAN MAKANAN - Suryana Purawisastra; Mien Karmini (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2002)
THE NEUTRALIZE EXAMINATION OF THE SPICES REACTIVITY IN THE IODIZED SALT BY THE ADDITIVE OF THE FOOD ADDITIVES.Background: The potassiumiodate of the iodized salt in the mixture with some spices is bind in the form of the compounds, which are not available for the determination of the iodine by the chemical method. This is due to the reactivity of susbtances contained inspices, such as capsaicin in the chilli, and piperine in the paprika, which are responsible for the spiciness of the spices. Although ithasn't been studied, the configuration of the potassiumiodate in the spices is probably also not available for the human consumption. Where as the supplementation of iodized salt to recover the iodine deficiency is effective. The food additives mostly are the chemical substances, which have properties to keep or increase the quality of food.Objectives: The study was performed to investigate the effect of food additives to the reactivity of spices to the potassiumiodate of iodized salt.Material and Methods: The food additive was added to the iodized salt, and then mixed with the spice. Dissolved by the water incertain volume, filtered, and then determined the potassiumiodate content of the filtrate by the Yodometric method. The potassiumiodate content of the filtrate was compared with the potassiumiodate content of the salt. The result of percent comparisonis the recovery of potassiumiodate when mixed with food additive and spice. The recovery of potassiumiodate was done for the different potassiumiodate content of iodized salt. The study was using CaCO3, KH2P04, MgS04, Na2C03, NaHP04, K-citrate, benzoat acid, dan Na-benzoat as food additives, and the red chilli, hot chilli, pepper and coriander.Results: The reactivity of the pepper and coriander to the potassiumiodate of the iodized salt could be netralized by the addition of CaCO3, KH2P04, MgS04, Na2CO3, NaHP04, K-citrate, benzoic acid, dan Na-benzoic. But for the red chilli and hot chilli were not allof them, these were for CaC03 K-citrate, and benzoic acid. It was shown by the value of recovery of potassiumiodate contents of the iodized salt. The netralization properties of food addives were increased by the increasing of the potassiumiodate content of the iodized salt.Conclusions: The addition of some food additives into the iodized salt is able to prevent the iodate content of the salt from there activity of subtances in the spice. The addition of food additives also can pick up moisture of salt resulting preventation of the salt particles clumping together and so keep the product free flowing.Keywords: potassiumiodate, spices, iodized salt